Answer:
12.3 months
Step-by-step explanation:
You want the number of months (m) such that ...
1 - 17% = (1 -1.5%)^m
Taking logarithms:
log(0.83) = m·log(0.985)
m = log(0.83)/log(0.985) ≈ 12.3 . . . . months
If we were to simplify this it would equal the same equation because this cannot be solved. Due to there being no like terms. We also need to know what x equals which there is no number given here to solve. Have a great day!
Answer:
The initial distance between Wade and Alexandra is 240ft.
They walk towards each other.
Alexandra walks twice as fast as Wade.
Now, because they are walking towards each other, when the distance walked by both of them equals 240 ft, they will meet.
Then:
if Wade walks z ft, Alexandra walks 2*z ft.
So we have the equation:
Distance that Wade walked + Distance that Alexandra walked = 240ft
z + 2*z = 240ft
3*z = 240ft
z = 240ft/3 = 80ft
They will meet when Wade walks 80ft.
Answer:
24
Step-by-step explanation:
Line segment ON is perpendicular to line segment ML. Line segment OM = 13 units in length, line segment PN = 8 units in length.
Circle O is shown. Line segments M O, N O, and L O are radii. Lines are drawn to connects points M and N and points N and L to form chords. A line is drawn from point M to point L and intersects line O N at point P. The length of O M is 13 and the length of P N is 8. Angle O P L is a right angle.
9514 1404 393
Answer:
(6,2)
Step-by-step explanation:
As is often the case with multiple-choice problems, you don't actually need to know the detailed working. You just need to know what the answer looks like.
When point X is dilated by a factor of 2 with point Z as the center of dilation, it will move to a location twice as far from Z. You can tell by looking at the graph that X' will be in the first quadrant, above and to the right of the location of X. The only sensible answer choice is ...
X' = (6, 2)
_____
<em>Additional comment</em>
X is a distance of X-Z = (4, 0) -(2, -2) = (2, 2) from Z Doubling that will put the image point a distance of 2(2, 2) = (4, 4) from Z. When this is added to Z, we find ...
X' = Z + (4, 4) = (2+4, -2+4) = (6, 2)